Eusko legegileak Toki autonomiaren inguruan egindako apustua: Toki autonomia Euskadiko Toki Erakundeei buruzko apirilaren 7ko 2/2016 Legean - Ortzi de la Quintana Ibáñez (Revista Vasca de Administración Pública, 2017)
It seems that during last years, local autonomy has yielded in favor of other principles as budget stability and financial sustainability. These are the principles that were bolstered by the last amendments on Local Administration. But last april it was published Act 2/2016 from April 7th on Local Entities of Euskadi and with it the Basque Autonomous Community has made and effort to bolster municipal autonomy. This Act is the consequence of that effort where in terms of the nature and conception that the Basque Autonomous community has over municipality, local autonomy has been fostered. Under the Act you can see expressions of that support that to this day stand and strengthen the local autonomy inspired by the European Charter of Local Autonomy. In this work we are going to deal with the local autonomy indicators and its expression within the Act on Local Entities.